Ific sig workshop: values in integrated care - Nick Zonneveld; Mirella Minkman (International Journal of Integrated Care, 2019)
Background: Integrated health and social care initiatives are being developed in many countries and settings. This development has been guided by substantial knowledge about integrated care interventions, ingredients and building blocks. In practice, integrated care initiatives are still looking for ways to further align collaboration and define desired quality. Therefore a better understanding of the underlying mechanisms that drive or hinder collaboration, behaviours, decision making and governance processes is necessary. To gain more insight into these factors, the Special Interest Group Values of Integrated Care develops knowledge about underlying values and principles of integrated care. Aims and Objectives: The workshop will inform and invite participants about IFIC’s Special Interest Groups, and specifically about the objectives and activities of the SIG on Values in Integrated Care. Furthermore, the participants will learn about the role of values as underlying mechanisms in integrated care. The workshop will walk the participants through the development process of a proposed set of values of integrated care, developed by conducting a systematic literature review and an international Delphi consensus study. Also, the applicability of values will be shown and discussed by using practice examples. Furthermore, the audience members will have to opportunity to participate in an exercise of applying the approach to their own local context. The participants will be divided into small working groups and given a template that can be applied to their own integrated care practice. The working groups will fill out the templates and discuss: 1) which values underpin their integrated care practice; 2) how these values drive collaboration and behaviours in their integrated care practice; and 3) what striking differences and similarities within the working group are. Also, options for application of these values in practice, policy or research and possible further steps will be discussed interactively. Format – 60 / 90 minutes 1. Room introductions - 5 minutes 2. Introducing IFIC’s Special Interest Groups – Prof. dr. Mirella Minkman - 10 minutes 3. Introducing Values in Integrated Care - Nick Zonneveld MSc. - 15 minutes - Systematic Literature Review - International Delphi Expert Study - Case study example      4. Group work - 20 minutes 5. Report back - 10 minutes Target audience: The workshop will be of interest to professionals, managers, policy- and decisionmakers working in integrated care, to learn about underlying mechanisms that can influence behaviour, collaboration, decision-making and governance processes. Also researchers can benefit from this workshop, as we introduce a different perspective in understanding integrated care. Learnings/Take away: The workshop participants will: Learn about IFIC’s Special Interest Groups, and participate in the activities of the SIG Values in Integrated Care are, and how to participate in the SIG; Gain insight in how a values-driven perspective can contribute to the understanding of integrated care; Gain new perspectives on their own integrated care practice and local context by looking from a values-driven perspective; Contribute to the SIG by discussing new steps in development.